Investigation of cold-active and mesophilic cellulases: opportunities awaited - Chavan, Sambhaji; Shete, Ashvini; Mirza, Yasmin; Dharne, Mahesh S. (Biomass Conversion and Biorefinery, 2023)
In the recent decade, the global demand and fuel prices have urged a need to track down an alternate resource. Second-generation (2G) biofuel from the lignocellulosic biomass (LCB) is trending as the fundamental alternative resource. Although LCB is the most abundantly available renewable resource, its commercialization into 2G biofuel technology is a major challenge. Efficient LCB hydrolysis requires a proper lignocellulolytic enzyme cocktail. In view to addressing this problem, several researchers are investigating for efficient enzymes to hydrolyze LCB. To date, there are very few commercial enzymes that aid in the breakdown of LCB, and these enzymes are traditionally isolated from culturable microbes. As only 1% of the microbes can be cultivated in the laboratory, the potentials of the uncultured remain under-explored. In the recent decade, advances in metagenomics using next-generation sequencing (NGS) technologies have revealed the vast diversity of hydrolytic enzymes and multiple domain proteins in the ecosystem. Aiming this, we focus our review on investigating efficient cold-active and mesophilic cellulases from the metagenome. India is an agro-based country with various climatic regions, ranging from warm and humid in the south to mild or moderate and cold or snowy in the Himalayan north; therefore, both cold-active and mesophilic cellulases are needed for LCB to ethanol. Along with downsizing, the conversion cost of LCB to fermentable sugars not only increases the enzymatic conversion but also increases the fermentation efficiency, which ultimately helps to commercialize the second-generation biofuel technology. Metagenomics is an evolving concept, and it has opened new horizons for the discovery of micro-organisms and new enzymes.
Keywords: cellulases; Glycosyl hydrolase; Lignocellulosic biomass; Metagenomics; simultaneous saccharification and fermentation